Efficient composite photocatalytic material based on MOF loaded CdS as well as preparation method and application of efficient composite photocatalytic material
By loading CdS on the MOF porous material, CdS/MOF composite photocatalytic material was prepared, which solved the problem of improving photocatalytic activity caused by CdS agglomeration phenomenon, and achieved the effect of efficient photocatalytic regeneration of coenzyme NADH.
Patent Information
- Application Number
- CN202411137677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-19
Smart Images

Figure CN119500268A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic materials, and in particular relates to a high-efficiency composite photocatalytic material based on MOF loaded CdS, and a preparation method and application thereof. Background Art
[0002] Enzyme catalysis has the advantages of high efficiency, specificity and mildness. Enzymes are mainly divided into six categories, among which oxidoreductases account for about 30% of all enzymes and are the most widely used enzymes. They show high catalytic efficiency in reactions such as carbonyl reduction, oxidation of carbon-hydrogen bonds, and cyclization of carbon-carbon double bonds. For the production of drug compounds, the enantioselectivity of oxidoreductases is crucial. For example, the P450 enzyme catalyzes the synthesis of (E)-4-chloro-1-phenyl-1-butene to (E)-1-chloro-4-phenyl-3-butene-2-ol, which usually requires a two-step reaction at a specific temperature and using hazardous chemical reagents in a chemical catalytic system.
[0003] Enzyme catalysis is a relatively green synthesis method. It is known that 80% of the reactions involving oxidoreductases require NADH. NAD(H) usually exists in two forms: oxidized and reduced, respectively. + and NADH. In the catalytic process, most oxidoreductases require one or more nicotinamide adenine nucleotides (NADH) as cofactors, and the regeneration of cofactors to drive the activation of oxidoreductases can also make new green drug synthesis reactions possible. However, NADH is usually continuously supplied during the reaction, resulting in relatively high application costs. Therefore, the study of an economical, green and sustainable NADH regeneration system is of great significance to the popularization and application of NADH in industry.
[0004] Semiconductor cadmium sulfide (CdS) is a catalyst that can photocatalytically regenerate the coenzyme NADH, but the CdS photocatalyst has the following shortcomings: its bandgap is 2.4eV, and it can be excited under light of a larger wavelength, effectively enhancing the absorption of natural light. Its defect is that after CdS is photoexcited, long-term illumination will cause CdS photocorrosion, which seriously restricts its photocatalytic activity; CdS is prone to agglomeration, resulting in a reduction in the contact area between the substrate and the photocatalyst, which is not conducive to the improvement of photocatalytic activity. Therefore, its application in the photocatalytic regeneration of the coenzyme NADH takes a long time and has a low yield. For example, the yield after 60 minutes of reaction is only 50.4%. Therefore, there is still a lot of room for improvement in the application of CdS in the photocatalytic regeneration of the coenzyme NADH. Summary of the invention
[0005] The present invention aims to provide a method for preparing an efficient composite photocatalytic material based on MOF loaded CdS, so as to solve the problem in the prior art that the photocatalytic material CdS is prone to agglomeration during the application process, which is not conducive to improving the photocatalytic activity.
[0006] In the first aspect, the present invention provides a method for preparing a high-efficiency composite photocatalytic material based on MOF loaded with CdS, comprising the following steps:
[0007] S1. Preparation of MOF porous materials;
[0008] S2, using the MOF porous material as a carrier, 2+ The solution is adsorbed onto the MOF structure;
[0009] S3, add S 2+ The solution and Cd adsorbed on MOF 2+ Combined to generate CdS, which is fixed on MOF;
[0010] S4. After drying, a composite photocatalytic material with CdS loaded on MOF as a carrier is obtained, which is named CdS / MOF.
[0011] Further optimization, S2 added Cd 2+ The solution and S3 were added with S 2+ After the solution was added, they were stirred for 2 to 5 hours respectively.
[0012] The present invention has the following beneficial effects:
[0013] 1. The introduction of MOF in the present invention effectively improves the particle size of CdS and inhibits the agglomeration of CdS.
[0014] The CdS / MOF composite material contains both the characteristic diffraction peaks of MOF and the characteristic diffraction peaks of CdS. Comparing the composite CdS / MOF composite material with the single phase CdS, the characteristic diffraction peaks of CdS in the CdS / MOF composite material are broadened, the particle size of CdS is significantly reduced, and the CdS particles are well dispersed on the MOF surface. This shows that the introduction of MOF can effectively improve the particle size of CdS, and the agglomeration of CdS is well suppressed, which also enhances the interaction between CdS and MOF.
[0015] 2. The CdS agglomeration phenomenon is inhibited, which helps to increase the contact area between the substrate and the photocatalyst and improve the photocatalytic activity.
[0016] 3. The obtained CdS / MOF is used for photocatalytic regeneration of coenzyme NADH, with rapid and high yield effects.
[0017] The inventors tested the photocatalytic regeneration performance of MOF, CdS and CdS / MO. The results showed that the pure MOF structure had no photocatalytic performance; CdS, the yield was only 50.4% in 60 minutes; while CdS / MOF performed very well. In just 8 minutes, the yield of photocatalytic regeneration of coenzyme NADH reached 67.2%. Compared with CdS, the time was significantly shortened and the yield was significantly improved, which significantly improved the economy, greenness and sustainability of the NADH regeneration system.
[0018] 4. The following two aspects illustrate that the method of the present invention is beneficial to the formation of the composite material.
[0019] (1) CdS / MOF composite material at 1179 cm -1 The absorption peak of CdS / MOF is relatively weaker than that of MOF because the interaction between CdS crystals and MOF forms a new stretching vibration absorption peak of sulfide group (SC), which is beneficial to the formation of the CdS / MOF composite material.
[0020] (2) The binding energies of Cd and S elements in CdS / MOF both move toward the low energy region. This phenomenon indicates that when CdS / MOF is formed, charge transfer occurs at the interface between CdS and MOF, and electrons move from CdS to ZnO, resulting in a close connection between MOF and CdS, which is conducive to the formation of the composite material.
[0021] 5. There is an interaction force between MOF and CdS, which makes the two closely connected.
[0022] The inventor characterized the morphology of CdS, MOF, and CdS / MOF by SEM. The results showed that CdS was a blocky substance composed of spherical particles with very small particle size. Single-phase CdS easily agglomerated to form larger aggregated CdS blocks. MOF showed a larger and regular crystal morphology. The MOF particle size was between 1.1 and 1.3 μm. There was no agglomeration of nanoparticles, and the MOF surface was relatively flat. The composite material loaded with CdS had obvious particles on the surface relative to the pure MOF, indicating that there was an effect of CdS embedding on MOF. The results of the element distribution diagram showed that the elements on the surface of CdS / MOF were evenly distributed, indicating that there was an interaction force between MOF and CdS, which made the two closely connected.
[0023] Furthermore, the preparation of the MOF porous material in S1 is as follows: a zinc salt solution is added to an imidazole aqueous solution to react and obtain the MOF porous material.
[0024] Furthermore, in S1, after a zinc salt solution is added to the imidazole aqueous solution for reaction, papain is added for modification, and then S2 to S4 processes are performed to prepare a composite photocatalytic material having a coating film on the outside, which is named CdS / MOF-P.
[0025] The CdS / MOF-P further prepared by the present invention has stable recycling and reuse performance. The prepared CdS / MOF-P is used for photocatalytic regeneration of NADH, with a yield of 66.5% in 10 minutes; after 28 cycles, the catalytic activity of dS / MOF-P remains basically unchanged, and the recycling performance is significantly improved compared with CdS / MOF, indicating that the cyclic stability of the photocatalytic composite material is enhanced after adding papain modification.
[0026] Furthermore, in S1, after adding papain to react, ethyl orthosilicate solution is added for mixed modification, and then through steps S2 to S4, the composite photocatalytic material finally prepared is named CdS / MOF-P / SiO2.
[0027] The CdS / MOF-P / SiO2 material further prepared by the present invention has better photogenerated electron-hole performance, indicating that the photosensitivity of the material is significantly improved after adding ethyl silicate modification. The CdS / MOF-P / SiO2 is used for photocatalytic regeneration of coenzyme NADH, and the photocatalytic efficiency is further improved. A higher yield can be obtained within 6 minutes, and the yield is as high as 72.6%. The reaction time is effectively shortened and the yield performance is improved. At the same time, the recycling rate of the composite material is significantly improved. The photocatalytic composite material CdS / MOF-P / SiO2 is subjected to a cyclic recycling test reaction of regenerating coenzyme NADH, and can be recycled 34 times.
[0028] Furthermore, the imidazole aqueous solution is a 2-methylimidazole solution, the zinc salt solution is a ZnAc solution; and the volume concentration of the ethyl orthosilicate solution is 5% to 10%.
[0029] Furthermore, the Cd 2+ Solution and S 2+ The amount of solution added was the same, and the molar concentration was 1 to 30 mmol;
[0030] The Cd-containing 2+ The solution includes one of CdSO4, CdCl2 or (CH3COO)2Cd·2H2O solution, S 2+ The solution includes one of Na2S, CH4N2S or C2H5NS solution.
[0031] Furthermore, in step S1, the reaction temperature is 5°C to 30°C, and in step S4, the drying temperature is 40°C to 80°C.
[0032] In a second aspect, the present invention also provides CdS / MOF, CdS / MOF-P and CdS / MOF-P / SiO2 composite materials prepared by the above method, which have high photocatalytic properties and are recyclable.
[0033] The MOF porous material described in the present invention has the characteristics of multiple surface adsorption sites, large specific surface area, and good conductivity. It can more stably adsorb and fix CdS to promote the transfer and utilization of electrons. Using such a MOF porous material to load CdS to obtain any of CdS / MOF, CdS / MOF-P and CdS / MOF-P / SiO2 can effectively improve the separation rate of photogenerated electron-hole pairs and the recovery and utilization rate of composite photocatalytic materials.
[0034] In the third aspect, any one of the CdS / MOF, CdS / MOF-P and CdS / MOF-P / SiO2 described in the present invention is applied to photocatalytic regeneration of NADH, which has the effect of significantly improving the yield performance in a short period of time.
[0035] The inventor tested the band gap values of CdS, CdS / MOF-P and CdS / MOF-P / SiO2, which were 2.24eV, 3.0eV and 2.98eV respectively. Compared with CdS, the band gap values of the composite photocatalysts CdS / MOF-P and CdS / MOF-P / SiO2 became larger, indicating that CdS / MOF-P and CdS / MOF-P / SiO2 can absorb light with higher energy. Under the condition of the same light intensity, photocatalysts with large band gap values have more opportunities to absorb light with higher energy, thereby stimulating more electron-hole pairs to promote the photocatalytic reaction. At the same time, the band gap values of the composite photocatalysts CdS / MOF-P and CdS / MOF-P / SiO2 in the present invention are large, which can reduce the recombination and loss of photoelectrons outside the illumination area and improve the efficiency of the photocatalyst. These characteristics are reflected in the performance and rate of photocatalytic regeneration of NADH.
[0036] Specifically, the high-efficiency composite photocatalytic material based on MOF loaded with CdS is applied to photocatalytic regeneration of NADH, comprising the following steps:
[0037] (1) the composite photocatalytic material and the coenzyme NAD + , electron donor, and Rh complex in a quartz test tube, and PB buffer was added to obtain mixture A;
[0038] (2) Place mixture A in a photoreactor, stir in the dark for 10 min, use 1.5A, 420nm blue light as the light source, and react to obtain NADH at a temperature of 15°C to 30°C.
[0039] Furthermore, the amount of the electron donor is 5 w / v% to 30 w / v%, preferably 5 w / v%; the electron donor is selected from one of triethanolamine, sodium ethylenediaminetetraacetate, ascorbic acid or methanol, the Rh complex is [Cp*Rh(bpy)(H2O)]2, the concentration is 0.1 to 0.5 mM, the concentration of the PB buffer is 0.1 M, and the pH value is 5 to 9.
[0040] In a fourth aspect, the coenzyme NADH obtained by the regeneration of the present invention is used in constructing a green drug synthesis system in which the regenerated coenzyme drives the P450 enzyme to catalyze the reaction of (E)-4-chloro-1-phenyl-1-butene to produce (E)-1-chloro-4-phenyl-3-butene-2-ol.
[0041] The regenerated coenzyme NADH obtained in the present invention is used for the first time to drive the P450 enzyme catalytic reaction to generate (E)-1-chloro-4-phenyl-3-butene-2-ol. As the concentration of regenerated NADH gradually increases, the yield of the product shows an increasing trend, which indicates that the regenerated coenzyme NADH has good biological activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 XRD patterns of pure CdS, MOF, composite photocatalytic material MOF-P, CdS / MOF, CdS / MOF-P and CdS / MOF-P / SiO2.
[0043] Figure 2 , Figure 3 They are HRTEM images and EDS mapping analysis images of CdS / MOF composite materials;
[0044] Figure 4 , Figure 5 They are HRTEM images and EDS mapping analysis images of CdS / MOF-P composite materials;
[0045] Figure 6 , Figure 7 They are HRTEM images and EDS mapping analysis images of CdS / MOF-P / SiO2 composite materials;
[0046] Figure 8 To investigate the cyclic stability of composite photocatalytic materials; (a) CdS / MOF; (b) CdS / MOF-P; (c-d) the number of photocatalytic material cycles with different CdS loadings in CdS / MOF-P;
[0047] Fig. 9 FTIR images of CdS, MOF-P, CdS / MOF-P and CdS / MOF-P / SiO2 composites;
[0048] Fig.10 (a) to (f) are SEM images of CdS, MOF, CdS / MOF, MOF-P, CdS / MOF-P and CdS / MOF-P / SiO2, respectively (the inserted images are taken at a higher magnification);
[0049] Fig.11 (a) is the full XPS spectra of CdS, MOF and CdS / MOF; (b) Zn 2p, (c) Cd 3d, (d) S2p, (e) C1s, (f) O 1s high-resolution narrow spectra;
[0050] Fig.12 XPS graphs of CdS, MOF-P, CdS / MOF-P and CdS / MOF-P / SiO2; (a) full spectrum of MOF-P and CdS / MOF-P; (b) full spectrum of CdS / MOF-P / SiO2; high-resolution narrow spectra of (c) Zn 2p, (d) O 1s, (e) Cd 3d, and (f) S2p;
[0051] Fig.13 EPR images of pure CdS, CdS / MOF-P and CdS / MOF-P / SiO2;
[0052] Fig.14 UV-VIS-NIR and tauc plots of pure CdS, CdS / MOF-P and CdS / MOF-P / SiO2;
[0053] Fig.15 Performance diagram of different conditions for the photocatalytic regeneration of NADH by CdS / MOF-P / SiO2, (a) CdS / MOF-P / SiO2 composite photocatalyst dosage screening; (b) screening of different pH values of the reaction solution PB buffer; (c) electron donor type screening; (d) triethanolamine (TEOA) dosage optimization; (e) Rh complex concentration optimization in the reaction; (f) spectral scanning;
[0054] Fig.16 The high performance liquid chromatogram and standard curve of (E)-1-chloro-4-phenyl-3-butene-2-ol. DETAILED DESCRIPTION
[0055] The following is further described in detail through specific implementation methods:
[0056] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0057] Embodiment 1, the preparation method of CdS / MOF composite photocatalytic material, the method comprising the following steps:
[0058] (1) Take a clean 500 ml beaker, mix 2-methylimidazole solution (0.8 M, 200 ml) and ZnAc solution (0.5 M, 20 ml), stir for 3 h, and wait for MOF to form;
[0059] (2) Add CdSO4 solution (5 mmol, 20 ml ddH2O) and stir for 3 h to allow the Cd in the solution to 2+ Adsorption on the MOF surface;
[0060] (3) Add Na2S solution (5 mmol, 20 ml ddH2O) and stir for 3 h to allow S 2- Fully compatible with Cd on MOF structure 2+ Adsorption-binding growth;
[0061] (4) Dry in a vacuum oven at 60°C, dry and grind to obtain CdS / MOF.
[0062] The CdS / MOF composite photocatalytic material can be prepared by replacing the CdSO4 in Example 1 with CdCl2 solution or (CH3COO)2Cd·2H2O, and replacing the Na2S solution with CH4N2S solution or C2H5NS solution, while keeping other components and steps unchanged.
[0063] Figure 1 The XRD spectrum of the CdS / MOF composite material prepared in Example 1 shows that CdS exhibits diffraction peaks at 2θ=26.5°, 44.0° and 52.1°, which correspond to the (111), (220) and (311) crystal planes in the diffraction pattern of the CdS sintered ore crystal structure (PDF#02-0454). Figure 1 There are two spectral lines of MOF and simulated MOF in the sample. The diffraction peaks displayed by the sample MOF correspond to the standard card PDF#00-062-1030; the CdS / MOF composite material contains both the characteristic diffraction peaks of MOF and the characteristic diffraction peaks of CdS. Comparing the composite CdS / MOF composite material with the single phase CdS, it can be found that the characteristic diffraction peaks of CdS in the composite are broadened, indicating that the particle size of CdS has been reduced.
[0064] Figure 2 and Figure 3 The HRTEM and EDS mapping of the CdS / MOF composite material prepared in Example 1 respectively show the microstructure and chemical composition of the CdS / MOF composite material clearly. Figure 2As shown, the MOF surface is combined with embedded CdS particles, and the lattice spacing is 0.21nm, which corresponds to the (220) crystal plane of the CdS crystal in the XRD spectrum; the crystal diffraction analysis results correspond to the (200), (311), and (222) crystal planes of CdS, confirming that the material is a composite material composed of MOF-loaded CdS nanoparticles. Through the EDS map ( Figure 3 ) It was observed that the elements C, Zn, N, and O on the surface of CdS / MOF and CdS / MOF-P composite materials originated from MOF, while the elements Cd and S originated from CdS, which is consistent with the XRD analysis results that MOF and CdS phases coexist in the composite. The element distribution diagram shows that the elements are relatively uniform, indicating that there may be an interaction force between MOF and CdS, resulting in a close connection between the two.
[0065] We characterized the morphology of CdS, MOF, and CdS / MOF by SEM, and we can clearly see that CdS is a bulk substance composed of spherical particles with very small particle size ( Fig.10 a), because single-phase CdS easily aggregates to form larger aggregated CdS blocks. MOF exhibits a larger, regular crystal morphology. It can be seen that the MOF particle size is between 1.1 and 1.3 μm ( Fig.10 b), there is no agglomeration of nanoparticles, and the MOF surface is relatively flat; the composite material loaded with CdS has obvious particles on the surface of pure MOF, indicating the effect of CdS embedding on MOF. However, the particle size of CdS in the CdS / MOF composite material is significantly reduced, and the CdS particles are well dispersed on the MOF surface, which is consistent with the XRD characterization. This shows that the introduction of MOF can effectively improve the particle size of CdS, and the agglomeration of CdS is well suppressed, which also enhances the interaction between CdS and MOF.
[0066] Fig. 9 FTIR images of CdS, MOF, and CdS / MOF, such as Fig. 9 As shown, CdS at 3450cm -1 and 1630cm -1 The absorption peak at 3450cm-1 can be explained as H2O in CdS. -1 It is the stretching vibration peak of -OH, 1630cm -1 The peak near this is the bending vibration peak of HOH. 1572 cm -1 Shows C=N stretching vibration, 1230-1460cm -1 The peaks in the range are stretching vibrations of CN, indicating the presence of organic ligand imidazole. -1The stretching vibration of C=O is the carbonyl bond of the enzyme in the MOF produced by papain, 1179 cm -1 The absorption peak at 1460 cm is usually attributed to the CH vibration of organic ligands. -1 With 1428cm -1 The absorption peak at 437cm is caused by the symmetrical stretching vibration of the CH bond. -1 The infrared spectrum of CdS / MOF composite material is similar to that of MOF, but it also contains the 1387cm in CdS spectrum. -1 、1110cm -1 、620cm -1 There are many characteristic absorption peaks. CdS / MOF composite material has a peak at 1179cm -1 The absorption peak of CdS is relatively weaker than that of MOF. The reason is that the interaction between CdS crystal and MOF forms a new stretching vibration absorption peak of sulfide group (SC), which is beneficial to the formation of the composite material.
[0067] The composite photocatalytic material CdS / MOF prepared in Example 1 was analyzed by XPS. Fig.11 As shown, the material mainly contains six elements: C, Zn, O, N, Cd and S. Among them, C, Zn, O and N elements come from the MOF phase, and Cd and S elements come from the CdS phase. This analysis result is consistent with the result obtained by EDS characterization. Fig.11 It can be seen that the C peak at 284.8 eV is used to calibrate the XPS data. Fig.11 b shows the Zn 2p spectrum. MOF has two strong peaks of Zn 2p3 / 2 and Zn 2p1 / 2 at 1021.1eV and 1044.1eV, respectively, corresponding to the Zn 2+ . Zn in CdS / MOF 2+ The binding energy position shifts are 1023.8eV and 1046eV respectively, and the binding energy increases. Fig.11 f) Analysis shows that the peak at 531.1 eV is attributed to the Zn-O bond, indicating the presence of ZnO in the photocatalytic material. Fig.11 c) and S2p peak ( Fig.11d) The binding energies are 412.1eV, 405.1eV and 162.1eV respectively, and the binding energies corresponding to the Cd 3d and S2p peaks in CdS / MOF are 411.2eV, 404.4eV and 161.1eV, indicating the existence of Cd-S bonds. The binding energies of Cd and S elements in CdS / MOF both move toward the low energy region, which is exactly opposite to the change of Zn 2p. This phenomenon shows that when CdS / MOF is formed, charge transfer occurs at the interface between CdS and MOF, and electrons move from CdS to ZnO, resulting in a close connection between MOF and CdS, which is conducive to the formation of composite materials.
[0068] The composite material CdS / MOF prepared in the above Example 1 is used as a photocatalyst in the regeneration of coenzyme NADH, and the application includes the following steps: 1 mM NAD + , 20mg photocatalyst, 10w / v% TEOA, 0.25mM [Cp*Rh(bpy)(H2O)]2, PB buffer (pH8.0, 0.1M) solution was added to 10ml and placed in a quartz tube, which was then placed in a photoreactor. The reaction was stirred in the dark at 25°C and 40rpm for 10min to reach the adsorption-desorption equilibrium of the mixture. The light source was turned on at 420nm and 1.5A for reaction. The reaction process was as follows: sampling and absorbance detection; the cyclic stability test steps of the photocatalyst; the photocatalyst in the regeneration reaction system was centrifuged and recycled, and the performance test was shown in Table 1 below.
[0069]
[0070] Table 1 Performance test of CdS / MOF photocatalytic regeneration of coenzyme NADH
[0071]
[0072] The pure MOF structure has no photocatalytic performance (Table 1, Entry 1); CdS (theoretical CdS loading of the composite material is 2.4 mg), the yield is 50.4% in 60 minutes, and it can only be recycled 9 times (Table 1, Entry 2); CdS / MOF, the yield is 67.2% in 8 minutes (Table 1, Entry 3), and the photocatalytic activity is completely lost after 4 cycles ( Figure 8 a), the next step is to improve the cyclic stability of the composite material by regulation and modification.
[0073] Example 2, preparation of composite photocatalytic material CdS / MOF-P.
[0074] Referring to the steps of preparing CdS / MOF composite materials in Example 1, papain was added in the preparation step (1) to prepare CdS / MOF-P. The specific step (1) is to take a clean 500 ml beaker, mix 2-methylimidazole solution (0.8 M, 200 ml) and ZnAc solution (0.5 M, 20 ml), and then add 1 to 5 g of papain, preferably 5 g of papain, and stir for 3 hours until MOF is formed.
[0075] The composite material CdS / MOF-P prepared in Example 2 is used for photocatalytic regeneration of coenzyme NADH. The photocatalytic regeneration reaction system of coenzyme NADH refers to Example 1. The cyclic stability test of the photocatalyst is shown in Table 2. The photocatalyst in the regeneration reaction system is centrifuged and recycled.
[0076] Table 2 Performance of CdS / MOF-P photocatalytic regeneration of coenzyme NADH
[0077]
[0078] Example 2: CdS / MOF-P was prepared for photocatalytic regeneration of coenzyme NADH, with a yield of 66.5% in 10 min (Table 2, Entry 2); the cycle stability test was as follows Figure 8 As shown in (b), after 28 cycles, the catalytic activity of the photocatalytic material remained basically unchanged, indicating that the cyclic stability of the photocatalytic composite material was enhanced after the addition of papain modification.
[0079] Example 2 CdS / MOF-P was prepared and XRD ( Figure 1 ) analyzed the crystal structure of the material. The addition of papain modification did not change the crystal structure of the composite material. HRTEM and EDS mapping ( Figure 4 and Figure 5 ) Analysis of the CdS / MOF-P microstructure prepared by adding papain in Example 2 shows that the composite material composed of MOF loaded with CdS has not changed, and the loaded Cd and S elements are evenly distributed; the morphology of the structure is characterized by SEM, as shown in FIG. Fig.10 (d-e), after adding papain to modify the material, the surface is wrinkled. The formation of the coating layer has a great effect on improving the stability of CdS / MOF, effectively wrapping the CdS nano-quantum dots on the surface of the material to prevent them from falling off during use; FTIR ( Fig. 9 ) analyzed the skeleton functional group structure of the material and found that the addition of papain modification did not change the internal structure of the material. The addition of papain effectively enhanced the cyclic stability of the material.
[0080] Further, the CdS loading of the CdS / MOF-P material was optimized to improve its photocatalytic performance. Specifically, on the basis of Example 2, different amounts of CdSO4 solution and Na2S solution (2.5, 5, 10, 15, 20, 25, 30 mmol) were added during the preparation process (the amount of CdSO4 solution and Na2S solution added was the same), and finally CdS / MOF-P composite materials with different CdS loadings were prepared, marked as 2.5-CdS / MOF-P, 5-CdS / MOF-P, 10-CdS / MOF-P, 15-CdS / MOF-P, 20-CdS / MOF-P, 25-CdS / MOF-P, 30-CdS / MOF-P. The prepared series of CdS / MOF-P composite materials were subjected to photocatalytic regeneration of coenzyme NADH. The photocatalytic regeneration of coenzyme NADH reaction system was referenced to Example 1. The cyclic stability test results of the photocatalyst are shown in Table 3.
[0081] Table 3 Performance of CdS / MOF-P photocatalytic regeneration of coenzyme NADH with different CdS loadings
[0082]
[0083] In Table 3, the yield of 5-CdS / MOF-P is 66.5%, which is the highest performance. The cyclic stability test of the material is as follows: Figure 8 (c~d), 2.5-CdS / MOF-P can be recycled and reused 21 times, the catalytic activity of 5-CdS / MOF-P remains basically unchanged after 28 cycles, 10-CdS / MOF-P can be recycled 42 times, and 20-CdS / MOF-P can be recycled more than 36 times; the optimization of CdS loading amount did not improve the catalytic performance, but it did improve the cyclic stability; based on the problem of improving catalytic efficiency, further regulation and modification were made based on the 5-CdS / MOF-P composite material.
[0084] Embodiment 3: A method for preparing a CdS / MOF-P / SiO2 photocatalyst, the method comprising the following steps:
[0085] (1) Take a clean 500 ml beaker, mix 2-methylimidazole solution (0.8 M, 200 ml), ZnAc solution (0.5 M, 20 ml), and 5 g papain, stir for 3 h, and wait for MOF to form;
[0086] (2) Add 10 ml of ethyl orthosilicate and stir for 3 h;
[0087] (3) Add CdSO4 solution (5 mmol, 20 ml ddH2O) and stir for 3 h to allow the Cd in the solution to 2+ Adsorption on the MOF surface;
[0088] (4) Add Na2S solution (5 mmol, 20 ml ddH2O) and stir for 3 h to allow S 2- Fully compatible with Cd on MOF structure 2+ Adsorption-binding growth;
[0089] (5) Dry in a vacuum oven at 60°C, dry and grind to obtain CdS / MOF-P / SiO2.
[0090] The performance test of CdS / MOF-P / SiO2 prepared in Example 3 for photocatalytic regeneration of coenzyme NADH is shown in Table 4. The reaction was carried out based on the reaction system of photocatalytic regeneration of NADH in Example 1.
[0091] Table 4 Performance of CdS / MOF-P / SiO2 photocatalytic regeneration of coenzyme NADH
[0092]
[0093] The data in Table 4 show that the photocatalyst was reacted with the composite material CdS / MOF-P / SiO2, and the reproduction rate of NADH was 72.6% in 6 minutes, and the photocatalytic efficiency was further improved.
[0094] Example 4: The composite material CdS / MOF-P / SiO2 for photocatalytic regeneration of coenzyme NADH in Example 3 was subjected to a cyclic stability test. Under the conditions of Example 3, the reaction system was enlarged to 20 mL, and 100 mg of photocatalyst was used. Other concentrations and conditions remained unchanged, and a cyclic stability test was performed.
[0095] Table 5 Cyclic stability test of CdS / MOF-P / SiO2 photocatalytic regeneration of coenzyme NADH
[0096]
[0097] Table 5 Cyclic stability test of CdS / MOF-P / SiO2 photocatalytic regeneration of coenzyme NADH
[0098]
[0099] The data in Table 5 show that the photocatalytic composite material CdS / MOF-P / SiO2 can be recycled 34 times in the recycling test reaction of regenerating coenzyme NADH. The loss of materials during the recycling process leads to a decrease in the overall catalytic activity.
[0100] CdS / MOF-P / SiO2 was characterized by XRD( Figure 1) analyzed the crystal structure of the material. The addition of ethyl silicate modification did not change the crystal structure of the composite material. HRTEM and EDS mapping ( Figure 4 and Figure 5 ) Analysis of the CdS / MOF-P / SiO2 prepared by adding papain in Example 8 shows that the microstructure of the composite material composed of MOF-loaded CdS has not changed, and the loaded Cd and S elements are evenly distributed; by FTIR ( Fig. 9 ) analyzed the skeleton functional group structure of the material. The modification did not change the internal structure of the material. The functional group of silicon-oxygen bond was added on the basis of the material prepared in Example 1. XPS ( Fig.12 ) analyzed the change in the binding energy displacement of the composite material. The change in the binding energy of the modified material was consistent with that of CdS / MOF, indicating that the interaction between the materials did not change. The morphology and structure were characterized by SEM, such as Fig.10 (f) After modification, the material becomes an irregular polyhedron. Analysis shows that the addition of ethyl silicate forms some silicon-oxygen bond compounds, which leads to irregular crystal formation. Then the photogenerated electron performance of the material is analyzed by EPR test, as shown in Fig.13 As shown, under the same test conditions, CdS / MOF-P / SiO2 has the best photogenerated electron-hole performance, indicating that the photosensitivity of the material is significantly improved after adding ethyl silicate modification, so that the photocatalytic efficiency is significantly improved.
[0101] Fig.14 The UV-VIS-NIR spectra and tauc diagrams of pure CdS, CdS / MOF-P and CdS / MOF-P / SiO2 are shown in Figure 2. Fig.14 As shown in a, the light absorption band edges of CdS, CdS / MOF-P and CdS / MOF-P / SiO2 are located at 592, 435 and 438 nm respectively. The absorption edges of the composite materials CdS / MOF-P (435 nm) and CdS / MOF-P / SiO2 (438 nm) are lower than the absorption edge of CdS (592 nm), indicating that the composite materials can absorb a wider spectrum than pure CdS. The tauc diagram obtained based on the analysis of the absorption spectrum is shown in Figure 1. Fig.14As shown in Figure b, the band gap values of CdS, CdS / MOF-P and CdS / MOF-P / SiO2 are 2.24eV, 3.0eV and 2.98eV, respectively, which is consistent with the results of UV-Vis diffuse reflectance spectroscopy. The larger the band gap value of the composite photocatalyst, the more it can absorb light with higher energy. Under the same light intensity conditions, photocatalysts with large band gap values have more opportunities to absorb light with higher energy, thereby exciting more electron-hole pairs to promote the photocatalytic reaction. At the same time, materials with large band gap values can also reduce the recombination and loss of photoelectrons outside the illumination area, thereby improving the efficiency of the photocatalyst. These characteristics can be reflected in the performance and rate of photocatalytic regeneration of NADH.
[0102] The CdS / MOF-P / SiO2 NADH regeneration reaction system was optimized. First, the dosage of the photocatalytic material (10 mg, 20 mg, 30 mg, 40 mg, 50 mg) was screened. Fig.15 a). The results showed that the yields of 10 mg, 20 mg, 30 mg, 40 mg, and 50 mg were 63%, 70%, 69%, 71%, 71%, and 71%, respectively. The results showed that when the catalyst dosage reached 20 mg or more, the yield of photocatalytic regeneration of NADH did not increase with the increase of catalyst dosage. Considering the economic cost, 20 mg was selected as the optimal photocatalyst dosage.
[0103] Based on the above CdS / MOF-P / SiO2 catalyst dosage of 20 mg, the pH value of the reaction solution PB buffer (pH 5.0, pH 6.0, pH 7.0, pH 8.0, pH 9.0) was screened ( Fig.15 b), the yields were 66.8%, 67.2%, 66.8%, 73.9% and 70.15% respectively. The results showed that under the same other conditions, the reaction was more suitable in a slightly alkaline solution of PB buffer solution. The yield of photocatalytic regeneration of NADH was relatively highest at pH = 8.0, 73.9%. Therefore, PB buffer solution pH = 8.0 was selected as the optimal reaction solution.
[0104] Based on PB buffer pH 8.0, the types of electron donors in the reaction (ascorbic acid (AA), methanol (MeOH), EDTA-4Na, triethanolamine (TEOA)) were screened ( Fig.15 c) The results show that under the same other conditions, the electron donor triethanolamine (TEOA) has the highest yield, so triethanolamine is the best electron donor for the reaction.
[0105] The amount of electron donor triethanolamine used in the reaction (5w / v%, 10w / v%, 15w / v%, 20w / v%, 25w / v%, 30w / v%) was screened ( Fig.15d), the results show that under the same other conditions, the amount of electron donor TEOA has no significant effect on the yield. Therefore, considering the economic cost, 5w / v% TEOA was selected as the optimal electron donor amount.
[0106] The electron donor in the reaction was triethanolamine, and the dosage was 5w / v%. The concentration of the electron mediator [Cp*Rh(bpy)(H2O)]2 in the reaction (0.1mM, 0.2mM, 0.25mM, 0.3mM, 0.35mM, 0.4mM, 0.45mM, 0.5mM) was screened. Fig.15 e), the results showed that the yields of the electron mediator [Cp*Rh(bpy)(H2O)]2 in the reaction were 0.1mM, 0.2mM, 0.25mM, 0.3mM, 0.35mM, 0.4mM, 0.45mM and 0.5mM, respectively, being 67.2%, 74.6%, 75.8%, 74.6%, 76.5%, 77.4%, 77.9% and 74.6%, among which the yield at 0.45mM concentration was the highest at 77.9%. Fig.15 f is the spectral scan of NADH photocatalytically regenerated by CdS / MOF-P / SiO2, which has a characteristic absorption peak of NADH at 340nm.
[0107] The NADH regenerated by CdS / MOF-P / SiO2 photocatalysis was used for P450 enzyme catalysis to generate (E)-1-chloro-4-phenyl-3-butene-2-ol from (E)-4-chloro-1-phenyl-1-butene. + Concentration groups (0mM, 1mM, 3mM, 5mM, 15mM), 20mg photocatalyst, 5% (w / v) TEOA, 0.25mM Rh complex, PB (pH 8.0, 0.1M) were added to 10ml, 100mg P450 enzyme, 0.5mM (E)-4-chloro-1-phenyl-1-butene, and the reaction was carried out for 12h. The reaction process is shown below. After the reaction, the sample was extracted with ethyl acetate solution containing 10mM phenylpropanol, and the yield was analyzed and calculated using HPLC and chiral column CHIRALCEL OD-H. Finally, the reaction yield of 2a was compared, as shown in Table 5.
[0108]
[0109] Table 6 Regeneration of NADH drives P450 enzyme catalytic reactions
[0110]
[0111] Photocatalytically regenerated coenzyme NADH is used to drive the P450 enzyme-catalyzed hydroxylation of (E)-4-chloro-1-phenyl-1-butene. +The concentrations of 0mM, 1mM, 3mM, 5mM, and 15mM were converted into NADH yields of 0, 70.4%, 65.2%, 64.2%, and 55.0%, and the corresponding regenerated NADH concentrations were 0mM, 0.69mM, 1.98mM, 3.24mM, and 8.25mM. The yields of (E)-1-chloro-4-phenyl-3-butene-2-ol produced by the P450 enzyme-catalyzed reaction driven by the regenerated coenzyme NADH were 10.3%, 11.1%, 20.5%, 24.9%, and 31.2%, respectively, as shown in Table 6. This regenerated coenzyme was used for the first time to drive the P450 enzyme-catalyzed reaction to produce (E)-1-chloro-4-phenyl-3-butene-2-ol. With the gradual increase in the concentration of regenerated NADH, the yield of the product 2a of the enzyme-catalyzed reaction showed an increasing trend, indicating that the regenerated coenzyme has biological activity. A green drug synthesis system was successfully constructed using a photocatalytic coenzyme to drive the P450 enzyme-catalyzed reaction of (E)-4-chloro-1-phenyl-1-butene to produce (E)-1-chloro-4-phenyl-3-butene-2-ol.
Claims
1. A method for preparing a high-efficiency composite photocatalytic material based on MOF loaded with CdS, characterized in that The following steps are involved: S1. Preparation of MOF porous materials; S2, using the MOF porous material as a carrier, 2+ The solution is adsorbed onto the MOF structure; S3, add S 2+ The solution and Cd adsorbed on MOF 2+ Combined to generate CdS, which is fixed on MOF; S4. After drying, a composite photocatalytic material with CdS loaded on MOF as a carrier is obtained, which is named CdS / MOF.
2. The method for preparing a high-efficiency composite photocatalytic material based on MOF loaded with CdS according to claim 1, characterized in that: The preparation of the MOF porous material described in S1 is: adding a zinc salt solution to an imidazole aqueous solution, and reacting to obtain the MOF porous material.
3. The method for preparing a high-efficiency composite photocatalytic material based on MOF loaded with CdS according to claim 2, characterized in that: In S1, after a zinc salt solution is added to the imidazole aqueous solution for reaction, papain is added for modification, and then S2 to S4 processes are performed to prepare a composite photocatalytic material having a coating film on the outside, which is named CdS / MOF-P.
4. The method for preparing a high-efficiency composite photocatalytic material based on MOF loaded CdS according to claim 3, characterized in that: In S1, after adding papain to react, 5% to 10% by volume of ethyl orthosilicate solution is added for mixed modification, followed by steps S2 to S4 to finally prepare a composite photocatalytic material named CdS / MOF-P / SiO2.
5. A method for preparing a high-efficiency composite photocatalytic material based on MOF loaded with CdS according to any one of claims 1 to 4, characterized in that: The Cd 2+ Solution and S 2+ The amount of solution added was the same, and the molar concentration was 1 to 30 mmol; The Cd-containing 2+ The solution includes one of CdSO4, CdCl2 or (CH3COO)2Cd·2H2O solution, S 2+ The solution includes one of Na2S, CH4N2S or C2H5NS solution; In step S1, the reaction temperature is 5°C to 30°C, and in step S4, the drying temperature is 40°C to 80°C.
6. A high-efficiency composite photocatalytic material based on MOF loaded with CdS, characterized in that: Prepared by the preparation method according to any one of claims 1 to 4.
7. Use of a high-efficiency composite photocatalytic material based on MOF loaded with CdS as claimed in claim 6 as a photocatalyst in the regeneration of coenzyme NADH.
8. The use according to claim 8, characterized in that: The following steps are involved: (1) the composite photocatalytic material and the coenzyme NAD + , electron donor, and Rh complex were placed in a quartz test tube, and PBbuffer was added to obtain mixture A; (2) Place mixture A in a photoreactor, stir in the dark for 10 min, use 1.5A, 420nm blue light as the light source, and react to obtain NADH at a temperature of 15°C to 30°C.
9. The use according to claim 8, characterized in that: The dosage of the electron donor is 5 w / v% to 30 w / v%, and the electron donor is selected from one of triethanolamine, sodium ethylenediaminetetraacetate, ascorbic acid or methanol. The Rh complex is [Cp*Rh(bpy)(H2O)]2, with a concentration of 0.1 to 0.5 mM. The concentration of the PB buffer is 0.1 M, and the pH value is 5 to 9.
10. Use of the coenzyme NADH regenerated according to the application of claim 8 or 9 in constructing a green drug synthesis system for regenerating coenzyme-driven P450 enzyme-catalyzed reaction of (E)-4-chloro-1-phenyl-1-butene to produce (E)-1-chloro-4-phenyl-3-butene-2-ol.
Citation Information
Patent Citations
CdS quantum dot / MIL-101 (Cr) composite material and preparation method and application thereof
CN113070042A
Doped CdS photocatalyst and application thereof in catalytic conversion of CO2
CN114515581A
Preparation method and application of CdS / Znln2S4 heterojunction photocatalyst
CN115739123A
Cadmium sulfide quantum dot-silica gel composite material as well as preparation method and application thereof
CN116116435A
Cited By
Fluorescent probe material for drug screening and drug screening method
CN120668619A